AGE-DEPENDENT ASPECTS OF ACUTE CORONARY HEART DISEASE INCIDENCE RATE AND MORTALITY IN MEN AND WOMEN - S. A. Boytsov; S. S. Yakushin; N. N. Nikulina; G. I. Furmenko; S. A. Akinina (Столичная издательская компания, 2016)
Aim. To study gender and age characteristics of incidence rate, mortality and lethality in acute coronary heart disease (ACHD).Material and Methods. Analysis of the ACHD (ICD-10 codes: I21.0-I22.9, I20.0, I24) morbidity, mortality and lethality, depending on sex and age was performed in the population (n=285 736; 46% men) of several city administrative districts of Voronezh, Ryazan and Khanty-Mansiysk. Morbidity, mortality and lethality were calculated on the basis of medical documentation as well as cases identified by the study protocol.Results. The ACHD morbidity and mortality in men were 1.99 and 1.79 times higher (p<0,001), respectively, than these in women. The studied parameters increase with age, reaching a maximum in 50-59 y.o., have a plateau in 60-79 y.o. and then they decrease. Morbidity and mortality in women increase with age, but reach a maximum in 70-79 y.o., being comparable with the male level, and then exceed it in ≥80 y.o. Age curve of lethality in men has J-alike shape with minimum in patients of 50-79 y.o. Women have a line age curve with minimum in patients of <50 y.o.Conclusion. The population of ACHD patients should be considered according to both the sex and age: <50, 50-79 and ≥80 y.o. Every of these population group has special epidemiological characteristics.